Comment on the Article “Regulating for Problematic Smartphone and Social Media Use Among Youth: A Public Health Challenge and Opportunity” - Elias, Cecília; Teixeira, Isabella; de Paraíso Camarinha, Catarina; Silva Costa, Andreia; Nogueira, Paulo Jorge (Acta Médica Portuguesa, 2026)
n/a.